PENINGKATANHASIL BELAJAR PADA PEMBELAJARAN MATEMATKA MENGGUNAKANTHINK PAIR SHARE DI KELAS IV SD - Audira, Mia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The purpose of this research is to improve student learning outcomes using a type of think pair share on mathematics learning materials determine KPK and GCF in the fourth grade Elementary School 54 West Pontianak. The method is used descriptively. Results of the study (1) Theability of teachers to design learning using a type of think pair share increased from the first cycle of meetings 1 3,15 0,18 to 3,33 medium category and the second cycle of meeting 1 3,41 0,1 to 3,51 high category. (2) The ability of teachers to implement the learning of mathematics using a type of think pair share increased from the first cycle of meetings 1 3,05 0,27 to 3,32 into the medium category and the second cycle of meeting increased 1 3,24 0,14 to 3,38 category being.(3) The average results of study in the first cycle of meetings 1 rose 75,78 80,31 4,53 into the excellent category, and the second cycle of meetings 1 increased 7,19 75,62 82,81 with very good categories. Conclusions using a type of think pair share to improve learning outcomes in mathematics at the fourth grade Elementary School 54 West Pontianak. Keywords: Improvement, Learning outcomes, Think pair share